Social-Ecological Correlates of Social Isolation as a Structural Indicator of Social Connectedness Among Young Adult U.S. Males. Issue 8 (November 2022) - Rovito, Kathy E.; Herring, R. Patti; Beeson, W. Lawrence; Gamboa-Maldonado, Thelma; Lee, Jerry W.
Purpose: We examined the intrapersonal, interpersonal, community, and societal correlates of a structural indicator of social connectedness (ie, social isolation) among a sample of young adult U.S. males Design: Cross-sectional. Setting: Online survey. Subjects: Males (n = 495) aged 18-25 years residing in the U.S. Measures: Social isolation was assessed as an index measure of social integration (inverse scored). The correlates consisted of the following variables: 1) intrapersonal (eg, social-demographic characteristics), 2) interpersonal (eg, adverse childhood experiences; marital status), 3) community (eg, county-level mental distress rates), and 4) societal (eg, how powerful is society's image of the 'masculine man'). Analysis: Four-block hierarchical regression. Results: The intra- and interpersonal variables significantly shared 17% and an incremental 5%, respectively, of the explained variance in social isolation. Several intra- (eg, financial vulnerability β = -2.76, [95% CI: -4.40, -1.13]) and inter-personal (ie, childhood household dysfunction β = -.66, [95% CI: -1.18, -.14] ) factors were significantly associated with greater social isolation. Four intrapersonal factors (eg, gay or bisexual β = 2.31, [95% CI: .29, 4.33]) were significantly associated with lower social isolation. Conclusions: The current study's findings have important implications for understanding and shaping social connectedness in young adult U.S. males, with micro-level influences potentially being most important in predicting social isolation in this population.